RESULTS OF STUDIES ON THE LEVEL OF POPULATION KNOWLEDGE ABOUT PARASITIC DISEASES AND ITS PREVENTION - Sadullayev S.E; Matyakubova O.U; Artikov I.A; Nurllayev R.R; Ibadullayeva S.S; Yakubov K.Y. (Western European Studies, 2023)
Only 1/3 of the respondents gave correct answers about the transmission pathways of parasitic diseases, which indicates their low level of knowledge about the transmission pathways of these diseases. The level of knowledge of the population about parasitic diseases common in the region is high compared to others (teniarinosis 21.1%, ascaridosis and giardiosis 19,5±1,4%, toxoplasmosis 17,8%±1,4%); Notably, there are more correct answers about food parasitic diseases (contaminated water 29.2%, meat and fish 32.9%) than about other transmission routes (soil-sand 23.7%, contact 29.2%)
Keywords: Helminths; route of infection; prevention